The concentrating mechanism in the renal medulla - Berliner, Robert W. (Kidney international, 1976)
The general nature of the process that is responsible for the formation of concentrated urine is well-known and little useful purpose would be served by reviewing it here. The subject is covered by a number of articles and book chapters that have been published in recent years [1–6]. Although for some years controversy has surrounded the question of the identity of the countercurrent multiplier, particularly in the inner medulla, it is now generally accepted that the loop of Henle is indeed the countercurrent multiplier, as originally proposed by Wirz, Hargitay and Kuhn [7], and that the thin segment of the loop constitutes the multiplier in the inner medulla. Further, little question remains concerning the view that the ascending thin limb is the source of the salt that is responsible for the increase in sodium and chloride concentration from the base of the inner medulla to the tip of the papilla. The most interesting question that remains concerns the nature of the process by which salt is transferred from the lumen of the thin ascending limb to the interstitium of the medulla. This in turn relates closely to the nature of the process by which solute is concentrated in the descending thin limb of Henle's loop as fluid flows from the outer medulla to the hairpin turn. This review will be concerned primarily with the various hypotheses that have been proposed in explanation of the multiplier function of the thin segment of the loop and the experimental observations that bear upon these hypotheses. Because of questions raised on morphological grounds concerning the capacity of the thin segment to behave as a countercurrent multiplier and because the earlier observations of the behavior of this segment left in doubt whether it possessed the permeability properties and the capacity for active transport that were presumed to be necessary for the multiplier function, a number of alternative mechanisms were proposed that would have placed responsibility for the concentrating function of the inner medulla in other structures [8–10]. Theoretical considerations or experimental observations or both made it apparent that none of these alternative proposals would account for the known properties of the inner medulla. When it was shown that the fluid in the thin ascending limb has a lower osmolality than fluid in the descending limb at the same level and that the deficit in osmolality was largely accounted for by the deficit in sodium chloride concentration [11] and further that the difference was attributable to removal of solute rather than addition of water [12], it seemed clear that the thin segment is indeed the counter-current multiplier. Active transport of salt out of the thin ascending limb seemed the only reasonable possibility despite the lack of success in attempts to detect such transport [13, 14]. This thinking perhaps reflected concentration on and attempts to adapt the counter-current multiplier models proposed by Hargitay and Kuhn [15] and Kuhn and Ramel [16] which derived their function from the movement of water driven by a hydrostatic pressure gradient or the transport of solute from one limb of the multiplier to the other. In fact, in the earlier model of Kuhn and Ryffel [7], no active transport of solute or movement of water in response to a difference in hydrostatic pressure was involved. Instead, the energy for driving the counter-current multiplier had been derived from the potential energy of a concentrated solution of a second solute. It is concerning this paper of Kuhn and Ryffel [7] that Wirz has appropriately said; “It is questionable that this paper was thoroughly studied by many who quoted it.” [4]. The principle embodied in the model of Kuhn and Ryffel is illustrated in Fig. 1. The recognition that the urine contained in the collecting ducts represents the concentrated solution of a second solute, urea, led Stephenson [18] and Kokko and Rector [19] independently and more or less simultaneously to propose models for the concentrating process in the inner medulla in which the movement of salt out of the ascending limb was facilitated by or even completely driven by favorable salt concentration gradients created by the presence of high urea concentrations in the medullary interstitium.1